Masyarakat Multikultural pada Masa Awal Perkembangan Islam di Nusantara: Sebuah Telaah Literatur - Een Syaputra; Ririn Selvianti (Tarikhuna: Journal of History and History Education, 2021)
This study aims to examine literature on Indonesian multicultural society during the Islamic Sultane era, especially from the 13th century until the arrival of the West in the 16-17th centuries. In particular, there are three aspects that will be the main discussion: 1) multicultural community; 2) relation with foreign nations; and 3) cultural exchange. This research was conducted with library research. The research steps undertaken are: 1) preparing tools and equipment; 2) compiling a working bibliography; 3) arranging research time; 4) reading and making research notes, and 5) concluding and analyzing the results of the research. The results of the research showed that: 1) during the Islamic Sultane, in Nusantara developed port cities, in which there were various foreign merchant communities such as Bengalis, Venetians, Turks, Arabs, Persians, Gujarat, Indians, Malays, Javanese, etc. This kind of thing happened in almost every Islamic Sultane, from Samudra Pasai, Aceh Darussalam, Demak, Banten to Sulawesi, Kalimantan, and Maluku; 2) during the Islamic Sultane, the people of the Nusantara experienced a change in perspective from inward-looking to outward-looking so that intense and broad relations were established with many foreign nations, not only Arab but also others. These relations take place not only in trade but also in education, politics, etc; 3) intense interaction with the nations makes the people of Nusantara acquainted with many cultural elements, resulting in a cultural encounter. This cultural meeting eventually gave birth to cultural acculturation in various fields, such as clothing, architecture, culinary, tradition, etc.